La storia di un politico controvoglia Frammenti - Sacconi, Guido (Firenze University Press, 2014)
The Italian newspaper "La Repubblica" once called him "the most private politician in Tuscany," and perhaps never was there such a fitting definition. In the era of "political posturing", when the appearance was worth more than the essence, the understatement characterising Guido Sacconi's not-so-short activity is even more surprising. A serious person, yet not an aloof one. This becomes easily understandable when reading this ironic reconstruction of politics 'as seen from the inside', made up of people in the flesh, with many strengths and flaws, who are mercilessly and tastefully described in these pages. In these same pages, Sacconi also has some bones to pick, which he must have collected during his career. Therefore, in a psychoanalytic key, Guido shows the Puer inside of him to those who have always seen him as a senex.